PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), LOAN TO DEPOSIT RATIO (LDR) DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) (Studi Empiris pada Perusahaan Bank Umum Konvensional yang terdaftar di BEI - Hanif, Ikhdan Fatih; Wijaya Z, Rico; Hernando, Riski (Jurnal Akuntansi Kompetif, 2025)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operating Expense to Operating Income Ratio (BOPO) on Return on Assets (ROA) in conventional commercial banks listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. Secondary data were taken from the annual financial reports of 29 banks with a total of 114 observations after removing outliers, using purposive sampling techniques. Data analysis was performed using multiple linear regression using IBM SPSS 26. The results showed that CAR and BOPO had a significant negative effect on ROA, while LDR had a significant positive effect. NPL had no significant partial effect on ROA. Simultaneously, all four variables have a significant effect on ROA. These findings emphasize the need for balanced management of capital, liquidity, credit quality, and operational efficiency to improve bank profitability. This study provides an important contribution to bank management and regulators in establishing policies to maintain the health and financial performance of the conventional banking sector in Indonesia. Keywords: Capital Adequacy Ratio, Non-Performing Loan, Loan to Deposit Ratio, Operating Expenses to Operating Income, Return on Assets